High-resolution crystal structures of ER aminopeptidase 1 with bound antigenic peptide precursor analogues. (October 2022) - Giastas, Petros; Lelis, Aggelos; Kokkala, Paraskevi; Georgiadis, Dimitris; Stratikos, Efstratios
Abstract : Objectives: ER aminopeptidase 1 (ERAP1) in an intracellular enzyme that optimizes the peptide cargo of Major Histocompatibility Class I molecules (MHC-I) and regulates adaptive immune responses thus being an emerging target for immunotherapy applications. It has unusual substrate selectivity, preferring longer peptides to shorter ones and its trimming rates are influenced by sequence, although no clear preference motifs have yet to be identified, hindering efforts to predict the enzyme's complex effects on the cellular immunopeptidome. To help understand the mechanism of substrate selection by ERAP1 we set out to crystallise the enzyme in complex with substrate analogues. Methods: We used x-ray crystallography to solve two structures of ERAP1 at 1.62 Å and 1.68 Å with bound two substrate analogues, one 15mer and one 10mer, designed based on ERAP1-sensitive antigenic peptide precursors. Results: The N-terminus of both peptides is found bound in the catalytic site resembling the transition-state intermediate formed during catalysis. Both peptides extend away from the catalytic site, along the internal cavity of the enzyme, making a series of atomic interactions that can influence selectivity. While both peptides extend along the base of domain II towards the domainII/domainIV junction, the 15mer diverges through the central region of the cavity and has its C-terminus stabilised in a pocket of domain IV by Tyr684, Lys685 and Arg807 in a manner reminiscent of carboxypeptidase recognition, while its middle portion is disordered. Conclusions: Analysis of the crystal structures suggests that the mechanism that underlies the unique specificity of ERAP1 revolves around sequence-dependent opportunistic binding in combination with specific C-terminal recognition for longer peptides. Our results provide a framework for understanding how ERAP1 influences the cellular immunopeptidome and adaptive immunity.